1 - Musique et danse chez les Haratin de Mauritanie : Conscience identitaire et/ou dissidence culturelle ? - Abderrahmane Ngaïde, (Afrika Zamani, 2022)
Mauritania is half way between sub-Saharan Africa and the so called ‘White Africa’. The country has been a cultural crossroad and negotiations. It produced new forms of sociability which gave birth to a hybrid culture the wealth of which is still not well known. The Haratin culture is still stifled because of several parameters related to the hierarchical basis of the Moor society. The local black people, found in the country or captured during razzias, have been turned into slaves and assimilated to the Arab culture. They keep deep within themselves the characteristics of a buried culture which expresses itself through their own music which sounds like American gospel. This article will select, structure the sounds and define the moaning of a yearning for freedom and of a sense of honour hidden in the medh (panegyric songs dedicated to the Prophet of Islam) and the redh, a type of songs and dances punctuated with tom-tom. Is it just a leisure activity or a culture production channel, a pressing desire for freedom or for integration into the host society or simply a desire to enjoy the Paradise delights promised to Muslims?